2020
DOI: 10.4070/kcj.2020.0131
|View full text |Cite
|
Sign up to set email alerts
|

Two-Sample Mendelian Randomization Study of Lipid levels and Ischemic Heart Disease

Abstract: Background and Objectives Associations between blood lipids and risk of ischemic heart disease (IHD) have been reported in observational studies. However, due to confounding and reverse causation, observational studies are influenced by bias, thus their results show inconsistency in the effects of lipid levels on IHD. In this study, we evaluate whether lipid levels have an effect on the risk of IHD in a Korean population. Methods A 2-sample Mendelian randomization (MR) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…With the introduction of new genetic techniques, many studies have found novel genetic variants in the field of cardiology. 9 Recently, genome-wide association studies (GWASs) have reported several genetic variants associated with AEs: for example, a study by the PREDICTION-ADR consortium on patients of European descent reported AE-associated single-nucleotide polymorphisms (SNPs) in a few novel genes, including GABRG2 . 10 In addition, several significant SNPs were identified in studies with different designs, such as GWAS discovery, replication, and meta-analysis.…”
Section: Introductionmentioning
confidence: 99%
“…With the introduction of new genetic techniques, many studies have found novel genetic variants in the field of cardiology. 9 Recently, genome-wide association studies (GWASs) have reported several genetic variants associated with AEs: for example, a study by the PREDICTION-ADR consortium on patients of European descent reported AE-associated single-nucleotide polymorphisms (SNPs) in a few novel genes, including GABRG2 . 10 In addition, several significant SNPs were identified in studies with different designs, such as GWAS discovery, replication, and meta-analysis.…”
Section: Introductionmentioning
confidence: 99%
“…25 These differences could be the reason that hypertriglyceridemia is an independent risk factor of cardiovascular disease in the Asian population. 26 , 27 Therefore, management of lipid levels, including TG, is particularly important in those of Asian ethnicity, 28 and fenofibrate-statin combination therapy could be an effective strategy to achieve this treatment goal.…”
Section: Discussionmentioning
confidence: 99%
“…The current strong interest in strategies to lower triglycerides in plasma is largely driven by the concept that this may attenuate atherosclerosis on top of cholesterol-lowering drugs. The support for this idea is provided by genetic studies that have recently suggested a causal link between increased levels of triglycerides and the risk of atherosclerotic cardiovascular disease (ASCVD) [2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%